Compressive responses of snap-fit Ti-6Al-4V octet-truss lattices in structure’s stiffest direction - Liang Dong (Materials & Design, 2021)
A snap-fit method has been designed to establish octet-truss lattice for which the through-thickness direction coincides with structure’s stiffest (crystallographic) direction. Sheet Ti-6Al-4V alloy of a single thickness was used as the starting material for the assembly of lattices which were subsequently brazed in vacuum to bond the nodes. Ambient temperature uniaxial compressive responses of the manufactured lattices have been investigated quasi-statically as a function of the lattice relative density, and are shown to be consistent with micromechanics predictions and finite element simulations. Analytical study reveals anisotropic-shaped biaxial failure loci in principal stress space, which expand anisotropically with an increasing relative density, and demonstrate greater structural strengths under tensile-tensile and compressive-compressive loading states. An assessment of structural efficiency has shown that the present snap-fit route is superior to our previously reported methodology in acquiring mechanically robust lattice performance for applications where maximum rigidity of octet-truss structure is sought. The present work has relaxed the plausible assumption that truss-plane-orthogonality relation must be satisfied for a specific topology to realize its snap-fit construction; incremental types of topology are thus feasible for snap-fit production characterized by versatility in material selection, cost-effective, and scale-up production capability.